PARADOX IN BUSINESS Towards a practical utility for paradox in business organizations - Mourad, Mechiche (My University, 2019)
Paradox studies offered vital and timely insights in the process of replacing the either/or thinking to both/and thinking. Regardless of this achievement, the paradoxical complexity of the paradoxical tensions has much increased in organizations due to the fast pace of change in these organizations on one hand. On the other hand, methods, approaches, strategies and models to attend to both the poles of a paradoxical tension seem to have maintained a theory driven stream. I use brain plasticity literature to unpack the knowledge on brain ability to adapt to chosen behaviour and alter itself on different levels even its structure to satisfy it. I used behaviour literature to support and complement the literature of brain plasticity that requires a behavioural change to incite the plasticity. Building on this literature, I develop an approach that helps combine the paradox theory literature with practice in a form of a practice utility that resembles a business simulation game, in which organizations’ executives practice and move up in mastery levels of managing the tensions of a paradox. Mixed research methods were used for this study. The empirical data were collected from a survey of 48 middle and senior level business executives. The insights of the empirical findings suggest a fair knowledge on paradox in business organizations, a will for a behavioural change towards an approach to managing paradox by practice. A digitized business simulation platform was chosen as the best form to present a utility to organization’s executives.
Keywords: Paradox; paradoxical thinking; managing paradox; practice utility; brain plasticity; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|